An Analysis of Students’ Learning Motivation at the Sixth Semester of English Language Education Program of Institut Pendidikan Tapanuli Selatan in 2020/2021 Academic Year - seri ayumisiregar seriayumisiregar (JURNAL LINER (Language Intelligence and Educational Research), 2021)
This research’ purposes are find: 1) the level of students’ learning motivation, 2) the type of students’ learning motivation. Research was conducted at the sixth semester of English Language Education Program of Institut PendidikanTapanuli Selatan in 2020/2021 academic year with respondent 23 students and 6 lecturers. This research use descriptive qualitative method. The data were collected through questionnaire that given to students through WhatsApp application and to lecturers directly. Triangulation was used in checking trustworthiness. The results of this study are 1). The level of students’ learning motivation at the sixth semester of English Language Education Program is “good category” and percentage is 79.87% based on source data from the students and 78.88% based on source data from lecturers. 2). The type of students’ learning motivation at the sixth semester of English Language Education Program is extrinsic motivation. It can be seen from the comparing of students’ extrinsic motivation from questionnaire that given to lecturers has percentage is 85.54% and students’ intrinsic motivation from questionnaire that given to students has percentage is 79.12%. It is can be conclude the level of students’ learning motivation at the sixth semester of English Language Education Program is “good category” and percentage is 79.87% and the type of students’ learning motivation at the sixth semester of English Language Education Program is extrinsic motivation from environment and percentage is 85.54%.